Delta intérieur du fleuve Niger au Mali – quand la crue fait la loi : l’organisation humaine et le partage des ressources dans une zone inondable à fort contraste. - Marie-Laure De Noray (VertigO)
In Mali, the inner Niger delta is a large, temporarily inundated wetland which covers approximately 35,000 km2 between the cities of  Djenne, Mopti and Tombouctou. One million people, especially fishers, cattle herders and flood recession farmers are using the delta for their subsistence or for export production. A sophisticated social organization allows each of these different user groups to exploit resources in the delta according to the flood pattern. As the environment moves through the annual flooding cycle, resource use in the delta is also influenced by two additional factors: one being the environmental degradation due to climatic events or human activities, the other linked to socioeconomic changes on the local, regional or global scale. These changes have much impact on the equilibrium between people and their environment. People must adapt to changes, but efforts are also made to both control and manage these changes.Using an historical and sociological perspective, this article describes the human organisation which characterised the main user groups in the delta. An analysis of the natural and human induced changes affecting the delta is also provided. Last, the main development issues and the role of research in supporting effective ecosystem-based management of the inner Niger delta are discussed.